2009
DOI: 10.3144/expresspolymlett.2009.61
|View full text |Cite
|
Sign up to set email alerts
|

Radiation processed ethylene vinyl acetate-multiple walled carbon nanotube nano-composites: Effect of MWNT addition on the gel content and crosslinking density

Abstract: Abstract. Different compositions of ethylene vinyl acetate (EVA)/multiple walled carbon nanotube (MWNT) nano-composites were prepared by melt mixing and subjected to different doses of gamma radiation. The efficiency of radiation vulcanization was analyzed by sol-gel analysis, Charlesby-Pinner parameter estimation and crosslinking density measurements. Gamma radiation induced crosslinking was found to increase with MWNT fraction in EVA-MWNT nanocomposites (p0/q0 in the range: 1.15-0.98). These results ruled ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
4
26
1
Order By: Relevance
“…23 We did not specifically investigate the influence of SDS concentration on the EG dispersion in our polymer, but all the experimental results presented in this article indicate improved dispersion of the EG after SDS treatment. Similar observations were reported by Dubey et al 24 in their study of radiation-processed EVA reinforced with MWCNT prepared via melt mixing. 22 This indicates that there was no EVA melting at a macroscopic level when the EB penetrated the polymer, and the EG or SDS-EG particles could not rearrange.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 89%
“…23 We did not specifically investigate the influence of SDS concentration on the EG dispersion in our polymer, but all the experimental results presented in this article indicate improved dispersion of the EG after SDS treatment. Similar observations were reported by Dubey et al 24 in their study of radiation-processed EVA reinforced with MWCNT prepared via melt mixing. 22 This indicates that there was no EVA melting at a macroscopic level when the EB penetrated the polymer, and the EG or SDS-EG particles could not rearrange.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 89%
“…Thus, the enhancement in the crosslinking yield after the MWNT incorporation can be attributed to the formation of multi-ionization spurs yielding Y-crosslinking and also increased possibility of spur overlap due to reduced free volume [22,23]. It can, therefore, be safely stated that neutralization of single ionization spurs, with increase in MWNT, is not significant in the present system.…”
Section: Resultsmentioning
confidence: 75%
“…The increase in magnitude of dE c /dV f (measure of reinforcement) with radiation indicates that there was improvement in the load transfer effect on irradiation and an interface link between MWNTs and elastomer matrix was established during radiation treatment. It is reported that, radiation induced cross-linking in the rubber-phases enhances the polymer-filler interaction [19,23], such an effect can also contribute to the observed dose dependent increase in the reinforcement (dE C /dV f ). These results support our justification that the higher crosslinking yield of nanocomposites containing higher fractions of MWNTs is due to physical crosslinking assisted free volume reduction in the nano-composite matrix.…”
Section: Mechanical Properties Of the Nano-compositesmentioning
confidence: 97%
“…In order to quantitatively evaluate the yields of cross-linking and chain scission of the NR/wood sawdust composites irradiated with EB, were drawn the plots of S + S 1/2 vs. 1/absorbed dose (D) from the Charlesby-Pinner equation for the different blend compositions (Figure 18) [55,56]: S+S=p0q0+1αPnD where, S is the sol fraction ( S = 1 − gel fraction), p 0 is the degradation density, average number of main chain scissions per monomer unit and per unit dose, q 0 is the cross-linking density, proportion of monomer units cross-linked per unit dose, P n is the number averaged degree of polymerization, and D is the radiation dose in Gy.…”
Section: Resultsmentioning
confidence: 99%